Co-Amorphous Formation of Simvastatin-Ezetimibe: Enhanced Physical Stability, Bioavailability and Cholesterol-Lowering Effects in LDLr−/−Mice - Shamuha Bahetibieke; Sakib M. Moinuddin; Asiya Baiyisaiti; Xiaoang Liu; Jie Zhang; Guomin Liu; Qin Shi; Ankang Peng; Jun Tao; Chang Di; Ting Cai; Rong Qi (MDPI AG, 2022)
Hypercholesterolemia is one of the independent risk factors for the development of cardiovascular diseases such as atherosclerosis. The treatment of hypercholesterolemia is of great significance to reduce clinical cardiovascular events and patient mortality. Simvastatin (SIM) and ezetimibe (EZE) are commonly used clinically as cholesterol-lowering drugs; however, their treatment efficacy is severely affected by their poor water solubility and low bioavailability. In this study, SIM and EZE were made into a co-amorphous system to improve their dissolution, oral bioavailability, storage stability, and cholesterol-lowering effects. The SIM-EZE co-amorphous solids (CO) were prepared successfully using the melt-quenched technique, and the physicochemical properties of CO were characterized accordingly, which exhibited improved physical stability and faster dissolution release profiles than their physical mixture (PM). In the pharmacokinetic study, the SIM-EZE CO or PM was given once by oral gavage, and mouse blood samples were collected retro-orbitally at multiple time points to determine the plasma drug concentrations. In the pharmacodynamic study, low-density lipoprotein receptor-deficient (LDLr−/−) mice were fed with a high-fat diet (HFD) for two weeks to establish a mouse model of hypercholesterolemia. Using PM as a control, we investigated the regulation of CO on plasma lipid levels in mice. Furthermore, the mice feces were collected to determine the cholesterol contents. Besides, the effect of EZE on the NPC1L1 mRNA expression level in the mouse intestines was also investigated. The pharmacokinetics results showed that the SIM-EZE CO has improved bioavailability compared to the PM. The pharmacodynamic studies showed that SIM-EZE CO significantly increased the cholesterol-lowering effects of the drugs compared to their PM. The total cholesterol excretion in the mouse feces and inhibitory effect on NCP1L1 gene expression in the mouse intestines after being given the SIM-EZE CO were more dramatic than the PM. Our study shows that the SIM-EZE CO prepared by the melt-quenched method can significantly improve the stability, bioavailability, and cholesterol-lowering efficacy with excellent development potential as a new drug formulation.